Effects of polyamidoamine dendrimers on the catalytic layers of a membrane electrode assembly in fuel cells - Lee, JH; Won, J; Oh, IH; Ha, HY; Cho, EA; Kang, YS (POLYMER SOC KOREA, 2006)
The transport of reactant gas, electrons and protons at the three phase interfaces in the catalytic layers of membrane electrode assemblies (MEAs) in proton exchange, membrane fuel cells (PEMFCs) must be optimized to provide efficient transport to and from the electrochemical reactions in the solid polymer electrolyte. The aim of reducing proton transport loss in the catalytic layer by increasing the volume of the conducting medium can be achieved by filling the voids in the layer with small-sized electrolytes, Such as dendrimers. Generation 1.5 and 3.5 polyamidoamine (PAMAM) dendrimer electrolytes are well-controlled, nanometer-sized materials with many peripheral ionic exchange, -COOH groups and were used for this purpose in this study. The electrochemically active surface area of the deposited catalyst material was also investigated using cyclic voltammetry, and by analyzing the Pt-H oxidation peak. The performances of the fuel cells with added PAMAM dendrimers were found to be comparable to that of a fuel cell using MEA, although the Pt utilization was reduced by the adsorption of the dendrimers to the catalytic layer.
Keywords: LOADING ELECTRODES; PLATINUM; TECHNOLOGY